Physiological Interference of Nanoemulsion-Formulated Botanical Insecticide Para-Menthane-3,8-Diol on Spodoptera frugiperda - Rayhan Fadhlurrahman; Eka Candra Lina; Novri Nelly (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
Para-menthane-3,8-diol (PMD), derived from citronellal of citronella plants, has potential as an eco-friendly botanical insecticide for controlling Spodoptera frugiperda. This study aimed to evaluate the physiological interference caused by a PMD nanoemulsion formulation on S. frugiperda. Bioassays were conducted using the leaf-dip method. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test with Statistix 8 and Duncan’s multiple range test at a 5% significance level using SPSS version 25. Probit analysis with POLO PLUS was performed to determine LC₂₅ and LC₅₀ values. The results showed that PMD nanoemulsion induced significant physiological interference in S. frugiperda, as indicated by increased mortality with LC₂₅ and LC₅₀ values of 0.15% and 0.48%, respectively. At a concentration of 0.75%, the treatment disrupted development by reducing pupation and adult emergence to 30% and altering the sex ratio to 1 male: 0.22 female. Sublethal interference was evident through strong antifeedant activity (62.88%) and pronounced changes in physiological parameters, including consumption rate (0.0328 mg/day), growth rate (0.0023 mg/day), and efficiency of ingested food (6.0029 mg/day). Overall, the PMD nanoemulsion formulation interfered with survival, feeding behavior, growth, and developmental physiology of S. frugiperda, highlighting its potential as an eco-friendly botanical insecticide.